Artesanato com Lixo Tecnológico - Xavier, Alda de Souza; Hortêncio, Claudomiro Braga; Carvalho, Elza Dias de Oliveira; Brito, Nilcéia Cezário de; Botassim, Rosa Maria Ferreira (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf